Low-temperature SCR activity and SO2deactivation mechanism of Ce-modified V2O5–WO3/TiO2catalyst - Ziran Ma Xiaodong Wu Ya Feng Zhichun Si Duan Weng Lei Shi (自然科学进展：英文版, 2015)
The promotion effect of ceria modi fi cation on the low-temperature activity of V2O5-WO3/TiO2 catalyst was evaluated for the selective catalytic reduction of NO with NH3(NH3-SCR). The catalytic activity of 1 wt% V2O5-WO3/TiO2 was signi fi cantly enhanced by the addition of 8 wt%ceria, which exhibited a NO x conversion above 80% in a broad temperature range 190–450 1C. This performance was comparable with 3 wt%V2O5-WO3/TiO2, indicating that the addition of ceria contributed to reducing the usage of toxic vanadia in developing low-temperature SCR catalysts. Moreover, V1 Ce WTi exhibited approximately 10% decrease in NOx conversion in the presence of 60 ppm SO2. The characterization results indicated that active components of V, W and Ce were well dispersed on TiO2 support. The synergetic interaction between Ce and V species by forming V–O–Ce bridges enhanced the reducibility of VCe WTi catalyst and thus improved the low-temperature activity. The sulfur poisoning mechanism was also presented on a basis of the designed TPDC(temperature-programmed decomposition) and TPSR(temperatureprogrammed surface reaction) experiments. The deposition of(NH4)2SO4on V1 Ce WTi catalyst was much smaller compared with that on V1 Ti.On the other hand, the oxidation of SO2 to SO3was signi fi cantly promoted on the CeO2-modi fi ed catalyst, accompanied by the formation of cerium sulfates. Therefore, the deactivation of this catalyst was mainly attributed to the vanishing of the V–Ce interaction and the sulfation of active ceria.